2018
DOI: 10.1016/j.immuni.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Inflammation with Myeloid Cell-Specific Nanobiologics Promotes Organ Transplant Acceptance

Abstract: SUMMARY Inducing graft acceptance without chronic immunosuppression remains an elusive goal in organ transplantation. Using an experimental transplantation mouse model, we demonstrate that local macrophage activation through dectin-1 and toll-like receptor 4 (TLR4) drives trained immunity-associated cytokine production during allograft rejection. We conducted nanoimmunotherapeutic studies and found that a short- term mTOR-specific high-density lipoprotein (HDL) nanobiologic treatment (mTORi-HDL) averted macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
188
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(214 citation statements)
references
References 45 publications
6
188
0
Order By: Relevance
“…Trained immunity could, in part, explain the epidemiological link between infections and atherosclerotic cardiovascular disease 143,144 . In addition to microbial products, endogenous triggers of innate immunity, including oxidized low-density lipoprotein particles, lipoprotein (a), vimentin and highmobility group box 1 (HMGB1), can induce trained immunity [145][146][147] .…”
Section: Pathological Outcomes Of Trained Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Trained immunity could, in part, explain the epidemiological link between infections and atherosclerotic cardiovascular disease 143,144 . In addition to microbial products, endogenous triggers of innate immunity, including oxidized low-density lipoprotein particles, lipoprotein (a), vimentin and highmobility group box 1 (HMGB1), can induce trained immunity [145][146][147] .…”
Section: Pathological Outcomes Of Trained Immunitymentioning
confidence: 99%
“…Another clinical scenario in which sterile endogenous stimuli could trigger trained immunity in monocyte-derived cells is organ transplantation 146 . Braza et al 146 recently showed in a mouse heart transplantation model that donor allografts upregulate vimentin and HMGB1, which induced local training of graft-infiltrating monocyte-derived cells. Short-term treatment with a high-density lipoprotein nanobiologic that specifically inhibited mTOR in myeloid cells was able to prevent aerobic glycolysis and epigenetic modifications underlying trained immunity.…”
Section: Pathological Outcomes Of Trained Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…This could be achieved, for example, by enhancing negative regulation of TLR signaling and silent clearance of apoptotic cells (33,(355)(356)(357)(358)(359), as well as by augmenting IL-10 receptor signaling (360)(361)(362). To note, thanks to their high phagocytic capacity, targeting intestinal Mfs could be facilitated by "delivery systems" such as nanomaterials and biomaterials (363), as has been shown in mouse model of organ transplantation (364).…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…Using a short-term regimen, long-term acceptance of the transplanted organ was achieved in the absence of serious side effects. 1 The nanomimmunotherapy consisted of high-density lipoprotein (HDL) nanobiologics, which they previously reported to specifically target myeloid cells in vivo. 2 In the current study, the authors demonstrate that HDL-nanobiologics target myeloid cells in the heart allograft and myeloid cell precursors in the bone marrow of transplant recipient mice.…”
mentioning
confidence: 99%